Association between limiting the number of open records in a tele-critical care setting and retract–reorder errors. (8th June 2021) - Udeh, Chiedozie; Canfield, Christina; Briskin, Isaac; Hamilton, Aaron C
Abstract: Background: Wrong patient selection errors may be tracked by retract–reorder (RAR) events. The aim of this quality improvement study was to assess the impact of reducing the number of concurrently open electronic health records from 4 to 2 on RAR errors generated by a tele-critical care service. Methods: The study encompassed 32 months before and 21 months after restriction. Chi-Square test of proportions and T statistical process control chart for rare events were used. Results: There were 156 318 orders with 57 RAR errors (36.5/100 000 orders) before restriction, and 122 587 orders with 34 errors (27.7/100 000 orders) after. Rates were not statistically different ( P  = .20), but analysis was underpowered. When plotted on a T control chart, random variation was detected between RAR errors. Conclusion: We found no significant difference in RAR errors in the tele-critical care setting after open record limitation. Other strategies should be studied to reduce wrong patient selection errors.